Electro-magnetic radiation of terahertz range, NO molecular specter frequencies, and coagulation hemostasis in patients with various angina forms - S. S. Parshina; V. F. Kirichuk; T. V. Golovacheva; T. N. Afanasyeva; V. D. Tupikin; A. P. Krenitsky; A. V. Mayborodin; N. A. Lopatina (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study hypocoagulation effectiveness and mechanisms of electro-magnetic radiation, terahertz range, NO molecular specter frequencies (EMR THF-NO), in patients with various angina forms. Material and methods. The authors examined 80 patients with unstable angina, Class IIA and IIB (E. Braunwald classification), or effort angina, Functional Class II-IV (Canadian Cardiovascular Society). Twenty patients received standard medication therapy plus EMR THF-NO. Noteworthy, EMR THF-NO effects in unstable angina (UA) were studied in the absence of heparin therapy. The effects on main hemostatic parameters were studied: activated partial thromboplastin time (APTT), activated recalcification time (ART), prothrombin time, euglobulin fibrinolysis, fibrinogen (F) levels, antithrombin-III (At-III) activity, complex parameter of protein C system disturbances, Va factor resistance to activated C-protein. Results. EMR THF-NO demonstrated hypocoagulation effect in patients with stable angina (SA) and UA. In SA, hypocoagulation mechanism is explained by procoagulation potential reduction, by affecting the first (APTT and ART increase) and the third (F level decrease) coagulation phases. In US, it’s explained by increase in anticoagulant potential, due to At-III and modulation of initially disturbed fibrinolysis. Conclusion. EMR THF-NO should be included into complex therapy of angina patients, for greater hypocoagulation effect. EMR THF-NO could be used as an alternative method in patients with hypercoagulation and contraindications to special pharmaceutical hypocoagulation, or intolerance to these medications.